ChemInform Abstract: A Strain Induced Change of Mechanism from a [2 + 2 + 2] to a [2 + 1 + 2 + 1] Cycloaddition Reaction. Issue 45 (23rd October 2014) - Tran‐Van, Anne‐Florence; Goetz, Silas; Neuburger, Markus; Wegner, Hermann A.
Abstract The reaction of macrocycle (I) with alkynes produces unexpected compounds (III) via formal [2 + 1 + 2 + 1] cycloaddition instead of the expected [2 + 2 + 2] cycloadducts.